Discovering untapped microbial communities through metagenomics for microplastic remediation: recent advances, challenges, and way forward - Wani, Atif Khurshid; Akhtar, Nahid; Naqash, Nafiaah; Rahayu, Farida; Djajadi, Djajadi; Chopra, Chirag; Singh, Reena; Mulla, Sikandar I.; Sher, Farooq; Américo-Pinheiro, Juliana Heloisa Pinê [UNESP] (Springer Nature, 2023)
Microplastics (MPs) are ubiquitous pollutants persisting almost everywhere in the environment. With the increase in anthropogenic activities, MP accumulation is increasing enormously in aquatic, marine, and terrestrial ecosystems. Owing to the slow degradation of plastics, MPs show an increased biomagnification probability of persistent, bioaccumulative, and toxic substances thereby creating a threat to environmental biota. Thus, remediation of MP-pollutants requires efficient strategies to circumvent the mobilization of contaminants leaching into the water, soil, and ultimately to human beings. Over the years, several microorganisms have been characterized by the potential to degrade different plastic polymers through enzymatic actions. Metagenomics (MGs) is an effective way to discover novel microbial communities and access their functional genetics for the exploration and characterization of plastic-degrading microbial consortia and enzymes. MGs in combination with metatranscriptomics and metabolomics approaches are a powerful tool to identify and select remediation-efficient microbes in situ. Advancement in bioinformatics and sequencing tools allows rapid screening, mining, and prediction of genes that are capable of polymer degradation. This review comprehensively summarizes the growing threat of microplastics around the world and highlights the role of MGs and computational biology in building effective response strategies for MP remediation.
Keywords: Biodegradation; Enzymes; Microorganisms; Plastic; Pollution